NOTES ABOUT THE SCOPE OF THE PRESENT INVESTIGATION ON THE LATIN AMERICAN AUTHORITARIAN STATE AND ITS SCHOOL - García, Natalia; Alfonseca Giner de los Ríos, Juan; Mateus Carreño, Tania (Historia y Memoria de la Educación, 2024)
The purpose of this paper is to provide a preliminary overview of the state of research on education as an instrument of domination during the «exceptional» moments assumed by the State throughout the 20th century in Latin America. This is a summary review mainly aimed at recovering part of the knowledge debated in the Ibero-American Congresses on the History of Latin American Education (CIHELA) in the last thirty years. Certainly, the universe of connotations that open up in this call outlined by the concepts «authoritarianism, violence, war, vulnerability and school», forces a limited theoretical-methodological operation and, for instance, affordable. In this sense, this work results from the search, identification, selection and analysis of a broad field of research and reflection on this subject, problems and academic objectives. Following the works presented in the CIHELA, this selection focuses on the transformations of the educational field, in general, and the school, in particular, in periods of restriction or closure of democratic participation. More specifically, it addresses the devices, uses and scope of authoritarian power according to the many variants assumed in each geography and unique history (foreign occupations, military and civil-military dictatorships, etc.).